2011
DOI: 10.1002/andp.201110472
|View full text |Cite
|
Sign up to set email alerts
|

Model of a relativistic oscillator in a generalized Schrödinger picture

Abstract: In a generalized Schrödinger picture, we consider the motion of a relativistic particle in an external field (like in the case of a harmonic oscillator). In this picture the analogs of the Schrödinger operators of the particle are independent of both the time and the space coordinates. These operators induce operators which are related to Killing vectors of the Anti de Sitter (AdS) space. We also consider the nonrelativistic limit.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
(8 reference statements)
1
4
0
Order By: Relevance
“…The results are also useful in the context of relativistic quantum mechanics. [69,70] We are able to show that this relationship is exactly as in the classical case, thus proving its thermodynamic ground, independent of the physical theory considered.…”
Section: Oscillation Frequency Of a Relativistic Anharmonic Oscillatorsupporting
confidence: 55%
“…The results are also useful in the context of relativistic quantum mechanics. [69,70] We are able to show that this relationship is exactly as in the classical case, thus proving its thermodynamic ground, independent of the physical theory considered.…”
Section: Oscillation Frequency Of a Relativistic Anharmonic Oscillatorsupporting
confidence: 55%
“…Here, in analogy to (11) for the external field which corresponds to a repulsive force we use the following operators…”
Section: Motion In a Two Dimensional Ds Spacetimementioning
confidence: 99%
“…In the paper [5], it was shown that equations like (5) may be used to describe a particle in an Anti-de Sitter spacetime. It was found that operators with an external field in the ρn-representation which corresponds to an attractive force induce operators K a (t, x i ) which are related to Killing vectors of the AdS spacetime (a = 1, 2, ...10; {x i }, i = 1, 2, 3.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] it has been shown that the ρn-representation may also be used in a so-called generalized Schrödinger picture in which the analogs of the Schrödinger operators of a particle are independent of both the time and the space coordinates in different representations. It was found that the operators H (ρ, n), P(ρ, n), L(n), and N(ρ, n) = ρn + (n × L − L × n)/2mc satisfy the commutations relations of the Poincaré algebra in the ρn-representation.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [4], this picture was used to describe the motion of a relativistic particle in anti-de Sitter spacetime (d = 2, d = 4). It was found that the spacetime independent operators of the particle in an external field (like in the case of a harmonic oscillator) induce the Lie algebra of Killing vector fields of the Ad S 4 spacetime (d = 4; a = 1, 2, .…”
Section: Introductionmentioning
confidence: 99%